BUDGET HOTEL DENGAN PENDEKATAN ARSITEKTUR HEMAT ENERGI DI COLOMADU, KARANGANYAR - Yusnia Satyawati Hardiningtyas; Bonifasius Heru Santosa Soemarno; Amin Sumadyo (Universitas Sebelas Maret Surakarta, 2016)
Colomadu is a locality of Karanganyar Regency located quite far apart from the Karanganyar Regency (exclave). Existing issues in the region of Colomadu becoming the background of planning and designing Budget Hotel in Colomadu with Energy Saving Architecture approach, as for instances, the existence of competition between hotels; a tendency of the tourist to stay in affordable lodgments with comfortable facilities; most of the hotels in Colomadu have not applied the concept of energy saving; as well as the Colomadu area good prospects and strategic location Budget Hotel since it is close to the International Airport of Adi Sumarmo and bounded by regions with capability to support activities in the Budget Hotel. The problem of the design is how to implement energy saving concept (focus on lighting and air conditioning system) on the building as an effort to minimize the expenses of energy use, but the facilities granted stay comfortable and affordable. The purpose of this design is getting a building design that provides lodging facilities with affordable, comfortable, and apply the concept of energy saving. The method used is the method of designing architecture with the Energy Saving Architecture approach. The results obtained, i.e. the design Budget Hotel with Energy Saving Architecture approach which is applied to the lighting and air conditioning system, such as determining the position of the openings and performing control of sunlight by providing massive walls, overhang, and secondary skin on the exterior of the building simulated with Autodesk Ecotect Analysis 2011 as well as the use of the roller blind or curtains in interior building, simulation system for Dialux 4.12 artificial lighting, and simple calculations to determine the system of artificial air conditioning (AC).